Valproic Acid–Induced Hyperammonemic Encephalopathy During Treatment of a Suicide Attempt in an Adolescent - Pombo, Diego (Revista del Hospital Italiano de Buenos Aires, 2026)
Introduction: self-harming behaviors and suicide in adolescence represent an increasing challenge in pediatric mental health. In Argentina, suicide accounts for 13.8% of deaths among individuals aged 10 to 19 years. While treatment is predominantly psychotherapeutic, moderate to severe cases may require psychotropic medications such as mood stabilizers. State of the art: valproic acid, used for its action on the GABAergic system, can induce metabolic adverse effects, including hyperammonemia and encephalopathy.Discussion: we present the case of an adolescent diagnosed with hyperammonemic encephalopathy associated with valproic acid use, with elevated plasma ammonia levels (584.4 µg/dL) and drug concentration (124 mg/L), in the absence of concomitant hepatic dysfunction. Discontinuation of valproate and initiation of levocarnitine therapy led to rapid clinical improvement and a reduction in ammonia levels. The pathophysiological mechanisms involved are discussed, including interference with mitochondrial metabolism, inhibition of the urea cycle, and the role of carnitine.Conclusion: this case highlights the importance of clinical suspicion and metabolic monitoring in the presence of neurological symptoms in patients undergoing treatment with valproic acid.